Human dignity as the basis of human rights - Martínez Loza, Carlos (2023)
This article deals with the study of human dignity as a concept that establishes the basis of the so-called human rights. To this end, the three classic and historical categories of dignity are analysed: ontological, theological and ethical. This is to achieve a better understanding of the positivist and iusnaturalist legal positions that try to find an answer to the first foundation of moral or human rights from a theoretical point of view.